2020
DOI: 10.1002/ajmg.a.61741
|View full text |Cite
|
Sign up to set email alerts
|

Short stature and growth hormone deficiency in a subset of patients with Potocki–Lupski syndrome: Expanding the phenotype of PTLS

Abstract: Potocki-Lupski Syndrome (PTLS, MIM 610883), or duplication of chromosome 17p11.2, is a clinically recognizable condition characterized by infantile hypotonia, failure to thrive, developmental delay, intellectual disability, and congenital anomalies. Short stature, classified as greater than two standard deviations below the mean, has not previously been considered a major feature of PTLS.Retrospective chart review on a cohort of 37 individuals with PTLS was performed to investigate the etiology of short statur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Human chromosome 17 is a small, gene‐rich chromosome associated with several well‐known duplication syndromes. So far the duplication region of 17p13.3p11.2 includes chromosome 17p13.3 duplication syndrome[OMIM:613215], 20 Charcot Marie Tooth Syndrome Type 1A (CMT1A), 21 and Potocki Lupski syndrome (17p11.2 duplication syndrome) 22 . Among these, 17p13.3 duplication syndrome 23 and Potocki‐Lupski syndrome 22 were reported to be related with CCA.…”
Section: Discussionmentioning
confidence: 99%
“…Human chromosome 17 is a small, gene‐rich chromosome associated with several well‐known duplication syndromes. So far the duplication region of 17p13.3p11.2 includes chromosome 17p13.3 duplication syndrome[OMIM:613215], 20 Charcot Marie Tooth Syndrome Type 1A (CMT1A), 21 and Potocki Lupski syndrome (17p11.2 duplication syndrome) 22 . Among these, 17p13.3 duplication syndrome 23 and Potocki‐Lupski syndrome 22 were reported to be related with CCA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying pathogenesis of GHD developmental defects is associated with pituitary dysplasia, Sella dysplasia and GH-IGF1 axis gene mutations, most genetic causes of GHD have not been identified, which may lead a certain false-negative rate in diagnostic approach. Recently, it has been reported that some patients with Potocki-Lupski syndrome or Prader-Willi syndrome have similar phenotypes as GHD patients ( 33 , 34 ), and recessive mutations in RNPC3 could also lead to the occurrence and development of GHD ( 35 ). In our study, we found seven genes ( PTPN11 , ROR2 , ACAN , COL11A1 , TRPS1 , IDS , MMP13 ) might associate with dysfunction of GH-IGF axis, indicating GHD may exist in a variety of Mendelian syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…In daily clinical practice, the question of growth deficiency predictably arises in children with common genetic disorders such as Turner syndrome, Down syndrome, and Noonan syndrome [ 19 ], or better known diseases as Diamond-Blackfan anaemia [ 20 ]. The diagnosis of growth deficiency due to growth hormone deficiency (GHD) in children with other genetic disorders is challenging, partly due to the lack of a true gold standard, and the relatively poor correlation of growth and the genes residing in the critical chromosomal locus [ 21 ].SDS is a rare disease without a well-defined prevalence. Severe growth retardation (particularly in length/ height) is one of its typical features, which can be alleged to be linked to the genetic cause of the disease [ 11 , 13 , 22 ].…”
Section: Discussionmentioning
confidence: 99%